The Regulation of International Navigation through the Northern Sea Route. Russian Legislation and International Law - Ergina, Natalia (UiT Norges arktiske universitet, 2014)
The objectives of this paper are to: examine and clarify the legal framework regarding the regulation of international navigation on the Northern Sea Route; determine and analyze policy and national legislation of the Russian Federation and its development since Soviet times; identify the international legal basis on which the position of the Russian Federation is based that support its unilateral regulation of international navigation on the Northern Sea Route, and last but not least analyze and assess this regulation with compliance or possible incongruence with the applicable international law, especially the International Law of the Sea.